Gender and Islam in Indonesian Studies, A Retrospective - Smith-Hefner, Nancy J. (Studia Islamika, 2025)
This essay considers continuities and discontinuities in the study of gender and Islam in Indonesia since the 1960s, tracing key themes that emerged early on and in many cases continue to animate contemporary scholarly discussion. Important themes include enduring patterns of matrifocality; the complementarity of gender roles; and the “essential bilateralism” of gender orders – which have led to assessments of the “relatively high status of Southeast Asian women.” This essay will focus on the impact of the resurgent interest in Islam on Indonesian gender studies from the 1980s until today, emphasizing the evolving status and role of women in the context of recent social and political developments and the rise of a new Indonesian Muslim middle class. It argues for the continuing importance of local, on-the-ground case studies that speak to broader regional patterns but also to Indonesia’s impressive ethnic and regional diversity.